Retrieving the postcolonial in NVM Gonzalea's A Season of Grace - French, Ma. Zenaida B. (2001)
A postcolonial reading of NVM Gonzalez's A Season of Grace would expand its value for Filipino readers and students of Philippine literature today. It would emphasize the effects of the colonial experience on the peasant sector of Filipino society who are the subjects of NVM's novel.
Keywords: Philippine literature -- Study and teaching; A Season of Grace (Novel)